Is Your Physical Education Adapted or Adaptive? - Laughlin, Michael K. (Journal of Physical Education, Recreation and Dance, 2025)
For decades, adapted physical education advocates have passionately engaged in a debate over two adjectives: adapted vs. adaptive. This article explores the reasons why one is preferred over the other and why it matters, especially to students with disabilities. © 2025 SHAPE America.
Keywords: dept.hms

Forgotten Learners: High School Transition Students With Disabilities - Laughlin, Michael K. (Journal of Physical Education, Recreation and Dance, 2026)
Because physical literacy and activity are not emphasized in special education as they are in physical education or adapted physical education (PE/APE), this editorial explores two important questions: Do high school transition students receive PE/APE programming? And are PE/APE teachers introduced or exposed to transition services at any point in their teacher training?. © 2026 SHAPE America.
Keywords: dept.hms

What’s Going on Out There? An exploration of K–12 PE Curricular Models and Content Taught in Public Schools - Hodges, Michael; Laughlin, Michael; Brusseau, Timothy (The Physical Educator, 2018)
Little is known about which curricular models and activity units are being taught in public schools. This exploratory study examined the K–12 physical education (PE) content and curricular models being implemented. Supervisors of PE recruited from one northeastern state participated in a 25-item questionnaire. Descriptive statistics and frequencies were calculated. Sixty-nine of 92 questionnaires were usable and included in the data analysis. Findings suggest that few districts were using a curricular model at the elementary (K–5) level (27%). Another common response of adopted curricular models at the elementary level was Movement Education (17.6%). At the secondary level, No Model (35%) and Fitness Education (25.6%) were common responses. Specific units such as volleyball, basketball, and weight training yielded the highest responses, while field hockey, golf, archery, lacrosse, and tennis yielded the fewest responses. The findings suggest that K–12 PE curricula may not reflect current trends and mandates. The key determinants could be a lack of curricular model use and heavy reliance upon activities known to present challenges toward standards-based education (i.e., softball). Perhaps K–12 PE and PE preparation programs can connect to effectively articulate a curriculum, and adopt and train on curricular approaches aiming to increase teacher effectiveness and reach national standards.Subscribe to TPE
Number: 5
Keywords: Content; Curricular Models; PETE; Units; dept.hms

Effects of an adapted physical education training package on special education teacher instruction - Laughlin, Michael K.; Murata, Nathan M.; McDougall, Dennis (Behavioral Interventions, 2019)
This study investigated the impact of an adapted physical education training package on functional motor skill instruction of three special education teachers who instructed secondary students with low-incidence disabilities. The training package emphasized teachers' use of systematic prompting and specific reinforcement teaching strategies plus adapted physical education consultation. We used a multiple baseline design and collected data on the three teachers' use of systematic prompting and specific reinforcement plans during videotaped teaching trials. We also collected data on how teachers documented their instructional strategies, and we analyzed personal reflections that teachers wrote in the journals. Results indicated that with each of the three teachers, correctly implemented functional motor skill instructional performance improved after they completed the training package.
0 citations (Crossref) [2023-10-31] _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/bin.1653
Keywords: dept.hms; functional motor skills; peer-reviewed; prompting; reinforcement; severe disabilities; special education

The Need for Accessible Health Education - Laughlin, Michael K.; Benes, Sarah; Sherlock-Shangraw, Rebecca (Journal of Physical Education, Recreation and Dance, 2026)
Health education in preschool through 12th grade is an essential component of a well-rounded education and can positively impact student health and well-being. All school-age students deserve access to high-quality, effective health education. However, students with disabilities may not be receiving the health education they are entitled to for many reasons, including that there is not a clearly defined understanding of health education for students with disabilities. Working from the perspective that health education is both a social justice imperative and an important component of students’ “well-rounded education” under the Every Student Succeeds Act of 2015, this article is a call to action and brings attention to this area of need. It is framed around three critical questions: (1) Why do students with disabilities deserve access to health education? (2) How should health education for students with disabilities be conceptualized? (3) Where does accessible health education go from here? By articulating these questions and providing initial thoughts to spur further discussion and action, this article encourages invested partners and collaborators to address this critical need so that students with disabilities can meaningfully access the same high-quality health education opportunities as their peers. © 2026 SHAPE America.
Keywords: dept.hms

Integrating edTPA into Physical Education Teacher Education: Teacher Educators’ Perceptions and Experiences in Preparing Teacher Candidates - Olsen, Edward B.; Wyant, James D.; Tsuda, Emi; Laughlin, Michael K.; Baxter, Deborah S. (Journal of Teaching in Physical Education, 2024)
Purpose: In the United States, 15 states maintain policies and 25 states represent some level of edTPA affiliation. This study investigated how the edTPA was integrated and aligned into different physical education teacher education (PETE) programs in New Jersey. It also sought to understand teacher educators’ perceptions and experiences in preparing teacher candidates for the edTPA. Methods: This study utilized three data sources: semistructured interviews (n = 4), one focus group interview (n = 1), and documents (n = 17). Data analysis reflected a conventional approach toward qualitative content analysis. Results: In analyzing the data, four themes were established: (a) benefits and drawbacks of edTPA in PETE, (b) goals and success of edTPA in PETE, (c) integrating edTPA into PETE—macro- and microperspectives, and (d) analytic insights into edTPA and future recommendations. Discussion/Conclusion: In states requiring the edTPA, early exposure, scaffolding, curriculum mapping, and a shared mission and vision are critical. In states not requiring the edTPA, programs may want to consider indicators of performance, such as artifacts, reports, elements of the edTPA, university-based assessments, or a portfolio. Regardless of the type of assessment, “a” performance-based assessment may help to determine teacher candidates’ ability to plan, instruct, assess, and reflect.
Keywords: dept.hms; faculty; peer-reviewed; performance-based assessments; preservice teachers